PENGARUH NILAI SUKUK, RATING SUKUK, UMUR SUKUK DAN RISIKO SUKUK TERHADAP YIELD SUKUK KORPORASI PADA TAHUN 2021 - Khairatul May Putri; Roza Linda (Jurnal Ekonomi Manajemen Bisnis Syariah dan Teknologi, 2023)
Sukuk yield is measure of the return that a sukuk investor will receive at maturity. This study aims to determine the effect of sukuk value, sukuk rating, sukuk age, and sukuk risk on corporate sukuk yield in 2021. The period used in this study was as long as one year. This research is quantitative research. The data used in this study are Secondary Data. Sampling in the study used purposive sampling. Data analysis in this study used cross section data regression with the help of spss 26. The corporate sukuk studied in this study is the mudharabah sukuk listed on the Indonesia Stock Exchange. Based on the results of partial test research. Sukuk Rating and Sukuk Age variables have a significant effect on Corporate Sukuk Yield in 2021. Meanwhile, Sukuk Value and Sukuk Risk do not have a significant effect on Corporate Sukuk Yield in 2021. The Coefficient of Determination in this study is 0.828, meaning that the Independent Variable in this study has a strong influence of 82.8% on corporate sukuk yield. The remaining 17.2% was explained by other variables outside the model.